The high-eccentricity asymmetric expansion of the disturbing function for non-planar resonant problems - Roig, F.; Simula, A.; Ferraz-Mello, S.; Tsuchida, M. (Edp Sciences S A, 1998)
In this paper we present an extension to the nonplanar case of the asymmetric expansion of the averaged resonant disturbing function of Ferraz-Mello & Sato (1989, A&A 225, 541-547). Comparions with the exact averaged disturbing function are also presented. The expansion gives a good approximation of the exact function in a wide region around the center of expansion.
Keywords: celestial mechanics; solar system : general; methods : analytical